2017
DOI: 10.1021/acs.inorgchem.6b02239
|View full text |Cite
|
Sign up to set email alerts
|

Specific Conformational Change in Giant DNA Caused by Anticancer Tetrazolato-Bridged Dinuclear Platinum(II) Complexes: Middle-Length Alkyl Substituents Exhibit Minimum Effect

Abstract: Derivatives of the highly antitumor-active compound [{cis-Pt(NH)}(μ-OH)(μ-tetrazolato-N2,N3)] (5-H-Y), which is a tetrazolato-bridged dinuclear platinum(II) complex, were prepared by substituting a linear alkyl chain moiety at C5 of the tetrazolate ring. The general formula for the derivatives is [{cis-Pt(NH)}(μ-OH)(μ-5-R-tetrazolato-N2,N3)], where R is (CH)CH and n = 0 to 8 (complexes 1-9). The cytotoxicity of complexes 1-4 in NCI-H460 human non-small-cell lung cancer cells decreased with increasing alkyl cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 51 publications
1
7
0
Order By: Relevance
“…These findings suggest that tetrazolato‐bridged dinuclear Pt(II) complexes, especially 7 , have the potential to become a basic skeleton for the next generation of antitumor drugs that can solve drug resistance of classical platinum drugs because of novel mechanisms. Komeda and co‐workers have made a thorough investigation to determine the mechanism of 7 and its derivatives (complexes 8 – 16 ; Figure ) . They found a U‐shaped association between alkyl chain length and cytotoxicity, where cytotoxicity decreased with increasing alkyl chain length up to an alkyl chain length of four or five, which agrees with the previous finding that this class of Pt(II) complexes with a bulky substituent at C5 are generally less cytotoxic than those with a small substituent.…”
Section: Multinuclear Platinum Complexessupporting
confidence: 78%
“…These findings suggest that tetrazolato‐bridged dinuclear Pt(II) complexes, especially 7 , have the potential to become a basic skeleton for the next generation of antitumor drugs that can solve drug resistance of classical platinum drugs because of novel mechanisms. Komeda and co‐workers have made a thorough investigation to determine the mechanism of 7 and its derivatives (complexes 8 – 16 ; Figure ) . They found a U‐shaped association between alkyl chain length and cytotoxicity, where cytotoxicity decreased with increasing alkyl chain length up to an alkyl chain length of four or five, which agrees with the previous finding that this class of Pt(II) complexes with a bulky substituent at C5 are generally less cytotoxic than those with a small substituent.…”
Section: Multinuclear Platinum Complexessupporting
confidence: 78%
“…Using fluorescence microscopy (FM) and atomic force microscopy (AFM), we elucidated the higher-order conformational changes of single long DNA strings induced by some novel cationic dinuclear Pt(II) complexes [29][30][31], which are potent anticancer drug candidates [32]. We found that these complexes shrink DNA much more efficiently than cisplatin.…”
Section: Introductionmentioning
confidence: 99%
“…Comparable results were obtained for cytotoxicity against L1210 murine leukemia cell lines [35]. Therefore, the introduction of bulky substituents tended to produce a lower in vitro cytotoxicity, possibly because the DNA interaction mode and cellular accumulation of complex 1 and 2 are distinct from those of 5-H-Y, and from other derivatives with a relatively small substituent at tetrazole C5 [34,45]. The cytotoxicity of oxaliplatin and complex 3 was markedly decreased in the presence of equimolar β-CD, whereas the cytotoxicity of 5-H-Y and complex 2 remained largely unchanged.…”
Section: Discussionmentioning
confidence: 89%
“…Tetrazolato-bridged complexes with the formula [{cis-Pt(NH 3 ) 2 } 2 (µ-OH)(µ-5-R-tetrazolato-N2,N3)] (NO 3 ) 2 (complexes 1-3, 5-H-Y) were prepared using previously reported methods [13,31,34,35]. Oxaliplatin and β-CD were purchased from Tokyo Chemical Industry (Tokyo, Japan) and Wako Pure Chemical (Osaka, Japan), respectively.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation